Husband's Support for Postpartum Mothers: A Correlation Study between Characteristics and Husband's Support f or Postpartum Mothers - Sari, Friska Fajar Khusnul Ambar; Rahayuningsih, Faizah Betty (Universitas Muhammadiyah Surakarta, 2022)
Purpose: To find out the description of husband's support for postpartum mothers in the Kartasura Health Center area.. Methodology: This study uses a quantitative descriptive method of research with a cross sectional approach. This study used the PSSQ (Postpartum Social Support Questionnaire) questionnaire consisting of 16 questions from Hopkins and Campbell (2008) which were translated into Indonesian. Results: The results of this study from 61 respondents found that all numerical characteristics showed no relationship with husband's support. Some categorical characteristics such as village, work, profession and intention to get pregnant show significant value with husband's support. Applications/Originality/Value: The difference between this study and previous research is the number of respondents, time and place of research, literature, theory used. The research is planned for health workers as literature in providing health education about husband's support for postpartum mothers.